2021
DOI: 10.1371/journal.pone.0253460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the implementation of carbon emission trading on corporate financial performance: Evidence from listed companies in China

Abstract: With the development of ecological paradigm coupled with the relentless implementation of myriad environmental policies in China, the rapid development of carbon emission trading and carbon trading market has had a vital impact on the financial performance of enterprises at the microlevel. This study has sampled the A-share listed companies in China, from 2009 to 2018, and adopted the difference-in-difference (DID) method to investigate the effect of the carbon emission trading on corporate financial performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…First, carbon emissions trading may bring additional benefits to firms. Liu et al (2021) show that carbon emissions trading policies increase the non-operating income of firms included in carbon emission controls. Meanwhile, existing studies find that carbon emissions trading may increase corporate total factor productivity (Peng et al, 2021), and improve their financial position and cash flow (Abrell et al, 2008;Oestreich and Tsiakas, 2015).…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 98%
“…First, carbon emissions trading may bring additional benefits to firms. Liu et al (2021) show that carbon emissions trading policies increase the non-operating income of firms included in carbon emission controls. Meanwhile, existing studies find that carbon emissions trading may increase corporate total factor productivity (Peng et al, 2021), and improve their financial position and cash flow (Abrell et al, 2008;Oestreich and Tsiakas, 2015).…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 98%
“…More and more countries, organizations, and enterprises are realizing the value embedded in CO 2 emissions rights. A CO 2 trading market based on allowances has gradually developed, giving rise to CO 2 emissions rights futures, options trading, and other financial products [38]. The ecological justice theory emphasizes the need for CO 2 emissions behavior to be organically integrated with social justice, working to unlock the international climate dilemma of collective action [39,40].…”
Section: Literature Review and Study Frameworkmentioning
confidence: 99%
“…For example, Liu et al (2021) showed that the implementation of carbon emission trading reduced the value of the current capital market. However, other studies have shown that the CET policy will enhance an enterprise's market value [4]. As carbon emission permits are freely allocated, the sale of the remaining permits could be accounted for by higher cash flows due to free permits, which would increase the market value of enterprises [5,6].…”
Section: Introductionmentioning
confidence: 98%